Pemberdayaan Tenaga Kependidikan Dalam Peningkatan Produktivitas Kerja Pegawai Di SMAN 1 Tasikmalaya - Sri Sulastri; Awang Kustiawan; Asep Budi Tauhid (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
Education personnel are part of educational resources, tasked with carrying out administration, management, development, supervision, and technical services to support the educational process. The success of the learning process in an educational institution is born from good management so as to produce good educational services as well. SMAN 1 Tasikmalaya is the first public school that was established in the city of Tasikmalaya since 1956, has made a myriad of achievements both academically and non-academically. This is not only supported by professional teaching staff but also supported by educational staff. In this research that used a qualitative descriptive method, it was concluded that increasing employee work productivity through empowering the education staff at SMAN 1 Tasikmalaya was categorized as good, because most of the education staff had carried out empowerment efforts starting from awareness, capacity building (enabling) and empowering ( empowering) is indicated by the achievement of empowerment indicators, namely access, participation, control and equality. This empowerment is carried out through (1) developing and realizing a shared vision, namely the 3K